The influence of parenting styles and thematic learning on the ethical relationship of Buddhist Sunday School students - Meto Sarono (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2021)
The aims of this research are that to determine the influence of parenting styles and thematic learning on the ethical relationship of Buddhist Sunday School students. Employing correlational qualitative research, this research was conducted at the Vihara Dewi Kwan Im Kayong Utara Buddhist Sunday School with 25 samples aged 12-18 years old. Determination of the sample in this study using non-probability sampling with saturated sample technique because the number of samples is below 30. Data collection is done by using a questionnaire technique. The collected data were analyzed sequentially with the prerequisite test for data analysis, descriptive analysis, classical assumption test, multiple linear regression test and effective contribution analysis. The results of the study show that: (1) parenting style has an influence on the ethical relationship of Buddhist Sunday School students with a significance of 0.004 and a tcount of 3.269 and is effective at 27.8 %; (2) thematic learning on friendship has an influence on the ethical relationship of students with a significance of 0.015 and tcount of 2.642 and effective reaching 18.9%; and (3) parenting style and thematic learning on friendship simultaneously have an influence on the ethical relationship with a significance of 0.001 and Fcount of 9,645 and R2 of 46.7%, which means that they are in the sufficient category. Based on the results of this study, the contributions of this study are to give beneficial awareness of appropriate parenting styles and the thematic learning on the ethical relationship for teenagers.